2019
DOI: 10.2486/indhealth.2018-0179
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of lumbar supports in low back functionality and disability in assembly-line workers

Abstract: Low back pain (LBP) is a common problem in manufacturing workers. Several strategies have been proposed in order to reduce the pain and/or improve functionality. Among them, lumbar supports are a common solution prescribed for lumbar pain relief. Most of the studies in the literature only consider subjective sensations of the workers for evaluation assessment. This study applies biomechanical tests (a flexion-relaxation test and a functional movement evaluation test) to analyse the effectiveness of flexible lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Therefore, physiotherapy because of being useful in strengthening lumbar muscles can increase the person’s ability to perform his/her daily activities, which confirms the results of previous studies 25,26 and current research to some extent. Regarding the orthosis effect, on the other hand, some previous studies reported no improvement in pain score or disability using rigid or semirigid LSO in persons with low back pain 16,27 . However, other studies reported improvements in these parameters by wearing LSOs 12,24 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, physiotherapy because of being useful in strengthening lumbar muscles can increase the person’s ability to perform his/her daily activities, which confirms the results of previous studies 25,26 and current research to some extent. Regarding the orthosis effect, on the other hand, some previous studies reported no improvement in pain score or disability using rigid or semirigid LSO in persons with low back pain 16,27 . However, other studies reported improvements in these parameters by wearing LSOs 12,24 .…”
Section: Discussionmentioning
confidence: 96%
“…Regarding the orthosis effect, on the other hand, some previous studies reported no improvement in pain score or disability using rigid or semirigid LSO in persons with low back pain. 16,27 However, other studies reported improvements in these parameters by wearing LSOs. 12,24 It should be noted that various disorders caused low back pain in previous studies, but the present study only evaluated people with low back pain due to herniation and that findings of the present study confirmed positive effect of LSOs, especially the semirigid type, along with routine treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the design of the spinal girdle specifically for brick-making industrial workers and its effectiveness has not been explored much. Several similar studies include the design of lumbar supports for assembly line workers (Bataller-Cervero et al, 2019), wearable lumbosacral support types for hospital workers (Hagiwara et al, 2017), designs of back belts aimed at preventing back pain due to prolonged sitting (Mokhtarinia et al, 2019).…”
Section: Nursing Practicesmentioning
confidence: 99%
“…In managing backache, most patients are commonly advised to use lumber support [16,17] to limit the impairment and disability, without expecting any long term adverse effect on muscle strength (18). In these days, many studies are supported by the lack of strong evidence that spinal orthosis prevents and improves the condition [19][20][21]. Nonetheless, the current trend among the medical practitioners is plummeting in advising to use the Lumber Corset (LC) without considering the large gaps between evidence and practices that persist in the management of LBA.…”
Section: Introductionmentioning
confidence: 99%